Supreme Court Circular Legislation Ratio Number 4 Of 2016 Related to Reserved Good Faith Buyer - Ihsan, Ahmad Yulianto; Hariri, Achmad; Stansyah, Dedy (Jurnal Hukum Replik, 2024)
The land sale and purchase dispute in this case drags the seller who has sold the same object to two buyers in two transactions. The second buyer (plaintiff) filed a lawsuit against the first buyer (Defendant II). The legal position is a dilemma. Both buyers feel they have rights to the disputed land because they have purchased the same object from the seller. To prove who the right buyer is, the judge needs to consider the principle of "good faith" as the basis for determining the buyer who deserves legal protection. The problem is, both buyers claim that they are buyers with good intentions. In protecting parties with good intentions in an agreement, regulations are needed that can provide legal certainty. In 2016 the Supreme Court held a plenary meeting and issued a Supreme Court Circular Number 4 of 2016, which provides a formulation regarding the criteria for buyers who have good intentions in purchasing land. In this study, it examines the first, the implementation of the Supreme Court Circular No. 4 of 2016 in court decisions. Second, the consideration of judges in deciding cases related to buyers in good faith is in accordance with applicable regulations. This type of research is normative research.